Assessment of knowledge, attitude and practice among house officers in UKM Medical Centre on needle stick injuries - Ahmad Syahmi Mohd Azman; Khairulini Mohd Amirol; Lee, Pei Chieh; Nurshafiqah Rosli; Nur Anis Nadirah Zulkifli; Khamsiah Nawawi; Nur Azlina Mohd Fahami (Penerbit Universiti Kebangsaan Malaysia, 2020)
Needle stick injury is one of the most serious occupational hazards among house officers in which it may lead to possible severe consequences such as HIV, Hepatitis B, and C infection. The aim of the study was to explore and compare the knowledge, attitude and practice (KAP) among house officers of UKM Medical Centre (UKMMC) regarding needle stick injury. A cross-sectional study was conducted with the total of 151 self-administered questionnaires from house officers in UKMMC within the period of five months. The data was collected via universal sampling method. Components evaluated were prevalence, demographic data and scores on KAP concerning needle stick injury among house officers. Out of the 151 house officers recruited for the study, 34.9% of them had a history of needle stick injury during their practice, with 6.7% of the injury that occurred in their current posting department. There was a significant association (p<0.05) between history of needle stick injury and the practice of house officers (p=0.035). House officers with a history of needle stick injury had a lower mean score of practice (8.65 ± 2.00) compared to those without history (9.40 ± 1.09). This study also demonstrated that there were significant correlations between Knowledge-Practice (r=0.194, p=0.018) and Attitude-Practice (r=0.182, p=0.026) of UKMMC house officers. These findings demonstrated that a good level of knowledge and attitude results in better practice of house officers hence reducing the incidence of needle stick injury. Therefore, suitable health education programs with regards to needle stick injury and preventive measures should be intensively implemented on all house officers prior to and during their practice.